Optimalisasi Integrated Digital Marketing dalam Strategi Pemasaran Home Industry di Desa Bandang Daja Kecamatan Tanjung Bumi - Aulia Dawam; Ruski Ruski (STKIP PGRI SITUBONDO, 2022)
This study aims to determine the optimization of integrated digital marketing in the home industry marketing strategy in Bandang Daja Village, Tanjung Bumi District. The population in this study are all home industry entrepreneurs who are in the village of Bandang Daja and are affected by the economy from the current COVID-19 pandemic, which amounts to around 10 entrepreneurs. The results show that in the future every home industry in the village of Bandang Daja chooses demographic, psychographic, and consumer behavior segmentation groups in digital marketing and does not only choose one segmentation. This digital marketing strategy will later be used to increase distribution or distribution that focuses on platforms, as well as a marketplace that provides several product details and is also equipped with a contact person which will contain the address of the instant messenger. It is also hoped that in the future the home industry in Bandang Daja village will carry out integrated digital marketing as the main marketing strategy to maximize sales and profits. Little by little and consistently the use of digital media really helps the home industry in the village of Bandang Daja in carrying out marketing functions effectively and efficiently as well as improving the economy during a pandemic that puts pressure on it like it is today.